Deciphering the spatiotemporal transcriptional and chromatin accessibility of human retinal organoid development at the single-cell level - Birthe Dorgau; Joseph Collin; Agata Rozanska; Veronika Boczonadi; Marina Moya-Molina; Adrienne Unsworth; Rafiqul Hussain; Jonathan Coxhead; Tamil Dhanaseelan; Lyle Armstrong; Rachel Queen; Majlinda Lako (iScience, 2024)
Summary: Molecular information on the early stages of human retinal development remains scarce due to limitations in obtaining early human eye samples. Pluripotent stem cell-derived retinal organoids (ROs) provide an unprecedented opportunity for studying early retinogenesis. Using a combination of single cell RNA-seq and spatial transcriptomics we present for the first-time a single cell spatiotemporal transcriptome of RO development. Our data demonstrate that ROs recapitulate key events of retinogenesis including optic vesicle/cup formation, presence of a putative ciliary margin zone, emergence of retinal progenitor cells and their orderly differentiation to retinal neurons. Combining the scRNA- with scATAC-seq data, we were able to reveal cell-type specific transcription factor binding motifs on accessible chromatin at each stage of organoid development, and to show that chromatin accessibility is highly correlated to the developing human retina, but with some differences in the temporal emergence and abundance of some of the retinal neurons.